Poly(methyl methacrylate) Nanoparticles Grafted with Gold‐L‐Cysteine as a Water Cleaning Material for the Photocatalytic Degradation of Paracetamol. Issue 30 (9th August 2022) - Agoudjil, Karima; Haddadine, Nabila; Davidson, Anne; Barama, Siham; Abouzeid, Khaled; Barama, Akila; Selmane, Mohamed; Bouslah, Naima; Benaboura, Ahmed; Barillé, Régis; Samy El‐Shall, M.
Abstract: Here, we report the photocatalytic degradation of aqueous paracetamol (Acetaminophen or N‐acetyl‐p‐aminophenol, APAP) as a drug model under visible light in presence of opal and inverse opal photonic crystals (PC) derived from gold‐L‐cysteine and grafted on poly(methyl methacrylate) (PMMA) nanoparticles. The L‐cysteine grafted PMMA colloidal nanoparticles with average diameters of 170 and 200 nm were prepared by emulsion polymerization. The reduction of the gold ions (HAuCl4 ) by L‐cysteine resulted in the formation of gold nanoparticles (AuNPs) attached to the PMMA colloidal particles. The opal photonic crystals Au@PC170 and Au@PC200, formed by self‐assembly of gold‐L‐cysteine‐PMMA nanoparticles, were treated by the sol‐gel method in the presence of a silica precursor. Therefore, two inverse opal photonic crystals (IOPCs): Au@SiO2 (1) and Au@SiO2 (2) were isolated following the polymer removal by calcination at 500 °C. The photocatalytic degradation of paracetamol (APAP) as a drug model was performed in the presence of the opal and inverse opal PCs. The results showed that 18.9 % of APAP photodegradation was obtained using the opal photonic crystals Au@PC200 after 2.5 hours, whereas 70.3 % of the photodegradation occurred instantaneously with the silica inverse opal photonic crystals Au@SiO2 (2). Consequently, the inverse opal photonic crystals were proposed as a potential effective water cleaning photocatalyst under visible light irradiation. Abstract : We report the development of novel opal and inverse opal photonic crystals derived from gold‐L‐cysteine and grafted on poly(methyl methacrylate) (PMMA) nanoparticles for the photocatalytic degradation of aqueous paracetamol (APAP) as a model drug under visible light. The inverse opal photonic crystals exhibit excellent photocatalytic activity and are proposed as a potential effective water cleaning photocatalyst under visible light irradiation.